Research on the Efficacy of Reciprocal Imitation Training for Children with Autism Spectrum Disorders - Kogutiak Nadiia; Mytsko Volodymyr (Insight: the psychological dimensions of society, 2023)
The aim of the research is to implement reciprocal imitationtraining on a Ukrainian sample, that is a promisingdirection for teaching imitation skills to childrenwith autism spectrum disorders (ASD) in a social-interactivecontext. A hybrid form of Reciprocal ImitationTraining (RIT) for families raising children with autismspectrum disorders is hypothesized to have demonstrableefficacy in reducing parenting stress and increasingparenting competence. Methods. An early intervention program and research on the use of reciprocal imitationgroup training for parents raising children with autismspectrum disorders are presented, aimed at increasingparental competence and reducing parental stress. Dueto pandemic restrictions, the training was deliveredin a hybrid (online and offline) format. The researchwas carried out in the fall of 2021. The study involvedtwelve families who had children with a clinical diagnosisof “Autism F84.0” according to ICD-10-CM, whichwas confirmed by STAT and ADOS-2 results. Results.There was a statistically significant difference inparental stress indicators =-2.24 (p≤.05) when the twopre-experimental (M1=111.59) and post-experimental(M2=70.16) sections were compared. A statisticallysignificant increase in the indicators of parental competencewas observed before and after the experiment(α=.05 t=-2.87). There were statistically significant differencesin the growth of general social communication(α=.05 t=-2.83) and social engagement (α=.05 t=-2.04)indicators of children’s social communication skills. Itshould be noted that no statistically significant differencesin the parameters of expressive communication,receptive communication, and imitation/game werediscovered. Discussion and conclusions. Positivebehavioral changes in children with autism spectrumdisorders, as well as a decrease in parental stress indicatorsand an increase in parental competence, havebeen experimentally proven and theoretically supported.To determine the effectiveness of the applicationof reciprocal imitation training on the Ukrainiansample, it is recommended that it be actively implementedand operationalized, with online and offlineformats verified.